(untitled) (Heritage, 2023)
In accordance with the development of Yugoslav-Turkish relations during the thirties of the twentieth century, and the close friendship between King Aleksandar Karadjordjevic and Turkish President Mustafa Kemal Ataturk, the Serbian press reported a lot in Turkey. In its reporting, the Serbian press popularized the image of Ataturk, comparing him to King Alexander. At the same time, in its reporting on Turkey, the press presented an image of the change of the Turks themselves, but in an ambivalent tone, which stemmed from the traditionally negative image of the Turks, shaped during the Ottoman rule in the Balkans.